(untitled) (ReAttach Affect Coach Journal, 2025)
It is understandable that when we are hurt, even when we try to forgive with our hearts, it is far more complicated to forgive and forget. If we retain sensory information excluded from processing, it remains, as it were, "before our retina," and therefore influences our perception and the behavior associated with it. Research links this disturbed perception inextricably to a broad spectrum of psychological and psychosomatic complaints. The ReAttach Forgive and Forget Hood (FFH) is an accessible tool for clearing the mind, helping us to place sensory information behind our eyes [1]. Recently, we published the first pilot studies examining the effectiveness of Forgive and Forget Hood in decreasing total burden and person-intolerance [2]. This paper presents a second effectiveness study on Forgive and Forget Hood, in which we also investigate the impact of the FFH on neuro-markers to help us understand the underlying mechanisms. In the discussion, we discuss the possibilities that this accessible, affordable self-regulation tool can offer as a first-aid psychological intervention.